CLPP Gene Variants Causing Perrault Syndrome Type 3 in Han Chinese Families: A Genotype-Phenotype Study - Xicui Long; Bingqian Yang; Wei Wang; Wan Peng; Xiaolu Wang; Wenyu Xiong; Man Liu; Huijun Yuan; Yu Lu (Human Genomics)
Abstract Background Perrault syndrome is a rare autosomal recessive disorder characterized by sensorineural hearing loss (SNHL) and primary ovarian insufficiency (POI) secondary to ovarian dysgenesis. However, the mutation spectrum of disease-causing genes for Perrault syndrome in the Chinese population remains poorly understood. In this study, we report on two Chinese families with Perrault syndrome type 3 caused by novel CLPP gene variants. We also conducted a comprehensive literature review of CLPP gene variants in Perrault syndrome type 3 to elucidate genotype-phenotype associations. Methods Using Whole Genome Sequencing (WGS) data, two pedigrees with Perrault syndrome type 3 were ascertained in the Chinese Deafness Genetics Cohort through genotype-driven analysis. Variants were validated using Sanger sequencing and copy number quantification methods. In vitro analysis of splice site variants in the CLPP gene using the minigene assay. Results Two Han Chinese families were ascertained: one with compound heterozygous variants (c.270 + 1G > C and c.355A > C [p. Ile119Leu]) and the other with missense variant (c.400G > C [p. Asp134His]) together with a large deletion in CLPP. In vitro minigene assays confirmed that the c.270 + 1G > C variant causes intron 2 retention and an alternative 5’ splice site in exon 2, leading to protein alteration. Among 33 Perrault syndrome type 3 patients in literature, 97% (31/32) had hearing loss, 55% (16/29) neurological disease, and 71% (15/21) females had POI. Including our 4 novel variants, 21 pathogenic CLPP gene variants have been reported, with 57% (12/21) missense and 43% (9/21) truncating variants, mainly in the ATP-dependent Clp protease proteolytic subunit. Biallelic truncating or missense plus truncating genotypes showed higher rates of neurological disease (p = 0.001), but no significant difference in hearing loss incidence compared to biallelic missense genotypes was observed. Conclusion This study highlights the challenges in diagnosing Perrault syndrome due to its genetically and clinically heterogeneity. By exploring novel variants and establishing genotype-phenotype correlations, we aim to improve the genetic diagnosis and consultation for this complex disorder.